As dinâmicas do mercado das coproduções cinematográficas entre Brasil e França - Figueiró, Belisa Brião (Universidade Federal de São Carlos, 2017)
This research investigates movie coproductions between Brazil and France, made between 1998 and 2014, trying to assess the percourse from the international co-elaboration to the distribution of such movies in the French circuit theaters. The analysis begins with the historical antecedents of cooperation, with the French protagonism in establishing policies to integrate and disseminate its culture, a model that influences countries around the world to this day. Next, we examine the attempts by Brazilian governments to reach the external market, the beginning of the historical approximation to France, the first official co-production agreement (1969) and the current one, signed in 2010. This study also presents a wide assessment of the Brazilian movies that were released in France, using data from Brazilian and French primary sources, and looks in depth at the release and repercussion in France of four study cases: Central do Brasil (1998), Abril despedaçado (2003), both by Walter Salles; O outro lado da rua (2006) and Meu pé de laranja lima (2013), both by Marcos Bernstein. The key questions this dissertation tries to answer are: how much coproduction in fact contributes to the opening of new markets; whether French coproductors influence in the distribution of the movie in their territory; and whether Brazilian policies have advanced beyond promotion and diffusion of movies in international festivals.
Keywords: Coprodução cinematográfica; Distribuição; Economia do audiovisual; Cinema brasileiro; Estado; Film coproduction; Distribution; Audiovisual economy; Brazilian cinema; Policy; LINGUISTICA, LETRAS E ARTES::ARTES::CINEMA::ADMINISTRACAO E PRODUCAO DE FILMES